The predictors of sales performance: a study with wholesale sellers - Donassolo, Paulo Henrique; Matos, Celso Augusto de (Review of Business Management, 2014)
Understanding which factors influence sales performance and how these factors vary in different contexts is essential both for managers and for researchers in the field of sales and marketing. Several studies have sought to identify the factors that exert most influence over the performance of salespeople. The importance of these factors may vary according to product type and the context in which sales are made. This paper seeks to test a model that consolidates a number of factors that influence sales performance of salespeople. In order to achieve these objectives, this paper addresses various models validated in other sales contexts and selects one of these to later test it by means of a descriptive study based on a survey conducted with 301 outside salespeople linked to wholesale companies located in different states of Brazil. The results obtained from the survey supported the adequacy of the model, which presented good fit indexes. The relationship between Self-efficacy, Effort and Performance has been confirmed and proved to be the main way that influences the performance of the salespeople. Both the academic and the managerial implications of these tests are presented and discussed in this paper.